2011
DOI: 10.1007/s10554-011-9930-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left atrial volume and function: a comparative study between echocardiography, magnetic resonance imaging and multi slice computed tomography

Abstract: Measurement of left atrial (LA) maximal volume (LA(max)) using two-dimensional transthoracic echocardiography (TTE) provides prognostic information in several cardiac diseases. However, the relationship between LA(max) and LA function is poorly understood and TTE is less well suited for measuring dynamic LA volume changes. Conversely, cardiac magnetic resonance imaging (CMR) and multi-slice computed tomography (MSCT) appears more appropriate for such measures. We sought to determine the relationship between LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 27 publications
6
65
1
Order By: Relevance
“…This is in contrast with all the other studies that have compared 2DE versus 3DE LA volumes and reported a 20% underestimation of LA volumes by 2DE in comparison to computed tomography and CMR. 3,4 We think that there may be several reasons for the differences between our study and earlier reports. In both previous studies, a software package designed for LV volume analysis was adapted to measure the LA volume by 3DE, whereas we have used a software specifically designed for LA analysis.…”
Section: Reference Values For La Volumescontrasting
confidence: 89%
“…This is in contrast with all the other studies that have compared 2DE versus 3DE LA volumes and reported a 20% underestimation of LA volumes by 2DE in comparison to computed tomography and CMR. 3,4 We think that there may be several reasons for the differences between our study and earlier reports. In both previous studies, a software package designed for LV volume analysis was adapted to measure the LA volume by 3DE, whereas we have used a software specifically designed for LA analysis.…”
Section: Reference Values For La Volumescontrasting
confidence: 89%
“…We have recently demonstrated that measurements of LA max and LA min in patients with permanent AF obtained by MDCT correlate closely with measurements obtained by CMR and that the reproducibility of both MDCT and CMR is superior to echocardiography [18]. Also, the reproducibility of MDCT in patients with AF is comparable to results previously reported for patients in SR [11,21], which suggests that application of 320-slice MDCT is indeed feasible in patients with AF.…”
Section: Discussionsupporting
confidence: 54%
“…Previously, a good interobserver agreement has been reported for measurements of LA volumes assessed by MDCT in SR patients [21]. …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, recent developments in MDCT have made it possible to visualize the LA in greater details, including wall characteristics and the PV size noninvasively with high spatial and reasonable temporal resolution by creating high-quality three-dimensional images [6]. This widely accessible imaging modality may be used to provide a more detailed anatomical evaluation and road map before ablation, in terms of both LA and PV anatomy [3,[7][8][9][10][11][12]. Recent studies indicate that LA and PV characteristics as determined by cardiac MDCT are possible important predictors of AF recurrence after ablation therapy [11,[13][14][15][16], and that the thicker the parts of the LA are, the less successful ablation therapy becomes [13,17].…”
Section: Left Atrial Wall Thickness (Lawt)mentioning
confidence: 99%